Aplicación web y móvil de vigilancia para el consumo de medicamentos en pacientes ambulatorios, utilizando “Fog Computing - Shiguango Garcia, Jonathan Cristoffer (2023)
During the COVID-19 pandemic, the lack of medication monitoring systems became evident, especially among the most vulnerable groups, such as older adults, children, and individuals with catastrophic illnesses. Many needed to adhere to medical prescriptions regarding timing and dosage correctly. To address this issue, a mobile application called "medical system" was proposed for development, integrated into an outpatient medication monitoring system. This application assists both patients and doctors by reminding them of medication schedules. Additionally, the doctor can obtain information about whether the patient is following medication guidelines, which are incorporated into their medical history and reviewed through the system's web interface. A LAN network environment was created using fog computing technology to achieve efficient communication. A centralized server supplies all the information to the medication monitoring system. An acceptable transmission speed of the information regarding medication doses patients take to the web-based dose manager has been observed. This implementation aligns with the advantages found in scientific articles researched during the project's development, such as a stable and efficient connection for the system. The use of fog computing technology in devices that interact within the Internet of Things (IoT) ecosystem, with a focus on healthcare, permits the avoidance of a constant connection to a cloud network, thereby avoiding latency issues and leveraging a connection to a local server. This benefits in terms of speed when adhering to assigned medication dose.